Numerical Solution of the Unsteady Incompressible Navier-Stokes Equations on the Curvilinear Half-Staggered Mesh (Journal of Computational Mathematics, 2000)
In this paper, the Crank-Nicholson+component-consistent pressure correction method for the numerical solution of the unsteady incompressible Navier-Stokes equation of [1] on the rectangular half-staggered mesh has been extended to the curvilinear half-staggered mesh. The discrete projection, both for the projection step in the solution procedure and for the related differential-algebraic equations, has been carefully studied and verified. It is proved that the proposed method is also unconditionally (in $Δt$) nonlinearly stable on the curvilinear mesh, provided the mesh is not too skewed. It is seen that for problems with an out flow boundary, the half-staggered mesh is especially advantageous. Results of preliminary numerical experiments support these claims.
Keywords: Unsteady incompressible Navier-Stokes equations; Curvilinear half- staggered mesh; Discrete projection.